Pseudotumoral presentation of fungating mycetoma caused by Phaeoacremonium fuscum in a renal transplant patient. Issue 6 (December 2015) - McGrogan, D.; David, M.D.; Roberts, C.; Borman, A.M.; Nath, J.; Inston, N.G.; Mellor, S.
Abstract: Eumycetoma is an unusual infection in immunocompromised patients outside the tropics, caused by a variety of fungal pathogens. We describe the case of a 51‐year‐old renal transplant recipient who presented with a large pseudotumoral foot lesion necessitating complete surgical excision of the lesion. Cultures and molecular diagnosis confirmed Phaeoacremonium fuscum . This is the first case, to our knowledge, of fungating mycetoma caused by this fungal species in a solid organ transplant recipient.